Jean-Baptiste, « une voix lointaine » - Sylvie Giraud (Flaubert: Revue Critique et Génétique)
In Gustave Flaubert’s Hérodias, Jean-Baptiste enters the tale’s framework long before his thundering entrance in chapter II, since from the start he is meant to play a decisive role, even as he remains invisible and anonymous. We will genetically analyze this first intervention of the preacher. Research in the “avant-texte” restitutes in its entirety the writing chronology of this episode, from the outline up to the final manuscript, thus revealing the whole construction in the details of its conception, structure and organization.